The Future of Islamic Studies in Indonesia: In Appreciation of IAIN-McGill Cooperation - Jabali, Fuad (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2001)
Dating from the establishment of the early Islamic kingdoms, Islam has been practiced in Indonesia for at least seven centuries. Through a gradual and continuous process, Islam has found its way into the hearts of the majority of Indonesians. This success is mainly due to the institutions that have been involved in studying and socializing Islam, including those newly established institutions such as IAIN (State Institute for Islamic Studies). Mosques and pesantren are of course the old institutions whose significant contribution to the development of Islam and the Muslim community are beyond doubt. Madrasah, which function in a similar manner to mosques and pesantren, are also important institutions, particularly in bridging the gap between Islam and modernity. But it is only at IAIN that a higher level and more sophisticated study of Islam is conducted in Indonesia. It is a natural expectation that IAIN will play a leading role in social transformation and community development in the face of complex challenges.DOI: 10.15408/sdi.v8i2.693